ADSORPTION KINETICS OF NICKEL IONS REMOVAL BY COCONUT FIBRE CHAR ADSORBENT - LOGANATHAN, KHUMANANARASU (IRC, 2017)
Rapid industrialization led discharging of heavy metal containing waste water into river stream. Pollution caused by this activity causes harm to both biological and human health. The famous heavy metal removal method via adsorption used by industries is limited due to high cost of preparation and availability of adsorbent. This project aims to study the usage of coconut fibre waste as the precursor for char adsorbent which is prepared by simple method of carbonization. The adsorption effect on temperature, contact time at different concentration and pH of stock solution have been studied to understand the adsorption capacity over different condition. This enables to provide knowledge on the nickel ion adsorption towards the studied characteristics of the char adsorbent. Where else, the adsorption kinetics focuses on the interpreting the adsorption behaviour of Ni (II) ions. The chemical process mechanism is depend on interaction via chemically between the adsorbate and the adsorbent. In order to evaluate these data, simple models such as pseudo first-order, pseudo second-order and Elovich are used to gather more knowledge on the adsorption process.